Host Phylogeny Is a Major Determinant of Fagaceae-Associated Ectomycorrhizal Fungal Community Assembly at a Regional Scale - Wu, Bin-Wei; Gao, Cheng; Chen, Liang; Buscot, François; Goldmann, Kezia; Purahong, Witoon; Ji, Niu-Niu; Wang, Yong-Long; Lü, Peng-Peng; Li, Xing-Chun; Guo, Liang-Dong (Frontiers in Microbiology, 2018)
Environmental filtering (niche process) and dispersal limitation (neutral process) are two of the primary forces driving community assembly in ecosystems, but how these processes affect the Fagaceae-associated ectomycorrhizal (EM) fungal community at regional scales is so far poorly documented. We examined the EM fungal communities of 61 plant species in six genera belonging to the Fagaceae distributed across Chinese forest ecosystems (geographic distance up to 3,757 km) using Illumina Miseq sequencing of ITS2 sequences. The relative effects of environmental filtering (e.g. host plant phylogeny, soil and climate) and dispersal limitation (e.g. spatial distance) on the EM fungal community were distinguished using multiple models. In total, 2,706 operational taxonomic units (OTUs) of EM fungi, corresponding to 54 fungal lineages, were recovered at a 97% sequence similarity level. The EM fungal OTU richness was significantly affected by soil pH and nutrients and by host phylogeny. The EM fungal community composition was significantly influenced by combinations of host phylogeny, spatial distance, soil and climate. Furthermore, host phylogeny had the greatest effect on EM fungal community. The study suggests that the assembly of the EM fungal community is governed by both environmental filtering and dispersal limitation, with host effect being the most important determinant at the regional scale.